Service Transformation as a Tool for Promoting Sustainable Rural Development in Central Java - Muhammad, Adji Suradji; Tyas, B. Hari Saptaning; Puspitasari, Condrodewi; Mardhika, Juang Gagah; Atmajha, Maulana Chandra (SCAD Independent, 2023)
The current developments in Information Technology (IT) should not only be utilized by the public and the private sectors but also by all parties effectively. The government must also be able to take advantage of these advances in many ways, such as in providing government services. The role of IT in managing government has now become an essential part of the society. This study examines the people's expectations in Melikan Village and focuses on using IT advances to create an independent village. The author then draws upon SDG theories to delineate the service transformation process. It is a qualitative study consisting of primary and secondary data. The data collection techniques used in this study include in-depth interviews, FGD, observations, and document analysis. The findings show that IT has become a vital need for the people in Melikan, but the village government fails to meet those expectations. The study suggests that the local government needs technological innovation to develop Melikan Village and add more personnel to help with government services.